2022
DOI: 10.1007/s11036-022-02042-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Security and Cyber-Security Risk Management within e-Health Systems: Synthesis, Analysis and a Novel Quantified Approach

Abstract: Internet of Things (IoT) applications are among the major trends of nowadays. Billions of connected devices are creating great business profits and performing a multitude of automated tasks in many daily human activities. In healthcare service delivery, IoT capabilities are difficult to overestimate, they are progressively becoming entangled and commonly coined Internet of Medical Things (IoMT). The participating nodes in IoMT networks generate, collect and exchange huge amounts of extremely private and sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The frameworks focus either directly on the IoMT and the healthcare sector or propose frameworks for the IoT in general, with an outline of possible applications in healthcare. 16 Upon examination of the full text, it was found that two papers by the same collective of authors 15 , 27 describe essentially the same framework. Both papers were included in the review because the authors in 15 describe the design of a risk management system falling under RQ 1, whereas paper 27 states that it is not only a method to enable operational risk management (falling under RQ 1), but also a risk assessment to help select the most suitable medical device from different alternatives, which falls under RQ 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The frameworks focus either directly on the IoMT and the healthcare sector or propose frameworks for the IoT in general, with an outline of possible applications in healthcare. 16 Upon examination of the full text, it was found that two papers by the same collective of authors 15 , 27 describe essentially the same framework. Both papers were included in the review because the authors in 15 describe the design of a risk management system falling under RQ 1, whereas paper 27 states that it is not only a method to enable operational risk management (falling under RQ 1), but also a risk assessment to help select the most suitable medical device from different alternatives, which falls under RQ 2.…”
Section: Resultsmentioning
confidence: 99%
“… 16 Upon examination of the full text, it was found that two papers by the same collective of authors 15 , 27 describe essentially the same framework. Both papers were included in the review because the authors in 15 describe the design of a risk management system falling under RQ 1, whereas paper 27 states that it is not only a method to enable operational risk management (falling under RQ 1), but also a risk assessment to help select the most suitable medical device from different alternatives, which falls under RQ 2. The risk calculation is described similarly, but the paper 27 additionally presents a method to calculate the risk probability, including examples of weights.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the size of the organizations or the complexity of the infrastructure used from a local building contractor to a massive, multinational company that manages everything, there is a procedure contained within the security policies. ISP comes into play during Intellectual Property (IP) or patent infringement cases, corporate espionage, and even intrusion events like a data breach or an instigated virus infection (Ksibi et al, 2022). For this purpose, the developed IISPM is a novel platform and can solve the heterogeneity, interoperability, and ambiguity of the ISP domain.…”
Section: Introductionmentioning
confidence: 99%